I smell creativity: exploring the effects of olfactory and auditory cues to support creative writing tasks - Gonçalves, Frederica (2022)
Humans perceive different objects, scenes or places using all their senses. Our sensory richness also plays an important role for creative activities. Humans also recall those sensory experiences in order to spark creativity, e.g. while writing a text. This paper presents a study with 100 students, divided in groups, that explores the effect of auditory and olfactory cues and their combina tion during a creative writing exercise. Our results provide useful insights sug gesting that olfactory cues have an important role in the creative process of users and even when this type of cues are combined with auditory cues. We believe, that this type of modalities should gain more relevance on the development of creativity support tools and environments for supporting the creative writing pro cess.